Q: What is 2x plus 9 equals 6x plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(2, 1)

6x - 3 = 2x + 1Add 3 to each side:6x = 2x + 4Subtract 2x from each side:4x = 4Divide each side by 4:x = 1

(2x-4)(x-1) = 0

3x(2x + 1)

x = -1

Related questions

6x + 3 = 2x + 5 4x = 2 x=1/2

(2, 1)

0.2x + 6x - 1 = -9 6.2x = -8 x = -1.2903225806451612903225806451613

6x - 3 = 2x + 1Add 3 to each side:6x = 2x + 4Subtract 2x from each side:4x = 4Divide each side by 4:x = 1

3x(2x + 1)

(2x-4)(x-1) = 0

x = -1

6x - 3 = 2x + 1Add 3 to each side:6x = 2x + 4Subtract 2x from each side:4x = 4Divide each side by 4:x = 1

6x - 9 + 2x + 1 = 8x -8

6x + 8 = 6 6x = -2 x = -2/6 x = -1/3

3(2x - 1)(x - 2)

The value of X in the equation 2x-1-6 5 plus 6x is -3.